2010
DOI: 10.1007/s12601-010-0001-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of decrease in salinity on the dynamics of abundance and the cell size of Corethron Hystrix (Bacillariophyta) in laboratory culture

Abstract: Effect of salinity on abundance dynamics and cell size of microalga Corethron hystrix Hensen (Bacillariophyta) were studied. C. hystrix can normally grow within a rather narrow salinity range between 32 and 28‰. The viable cells of this microalga change their morphological characters at a salinity of 24‰. This salinity level probably marks the beginning of cell division restriction, because the general number of cells by the end of the experiment was lower than in the control. The decrease of salinity to 16‰ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…We attribute this decrease to cell damage rather than acclimation due to the fact that abnormal cells were commonly observed at the beginning of the ice-melt period (Supplementary Figure S2). Similar cell deformation was also found in the large marine centric diatoms Ditylum brightwellii and Corethron hystrix when the cells were exposed to low salinities (Rijstenbil et al, 1989;Aizdaicher and Markina, 2010). For both species, lower salinity caused significant shrinkage of cytoplasm.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…We attribute this decrease to cell damage rather than acclimation due to the fact that abnormal cells were commonly observed at the beginning of the ice-melt period (Supplementary Figure S2). Similar cell deformation was also found in the large marine centric diatoms Ditylum brightwellii and Corethron hystrix when the cells were exposed to low salinities (Rijstenbil et al, 1989;Aizdaicher and Markina, 2010). For both species, lower salinity caused significant shrinkage of cytoplasm.…”
Section: Discussionsupporting
confidence: 70%
“…Cytoplasm strands and chloroplasts moved to the center or edge of the cells in D. brightwellii (Rijstenbil et al, 1989). For C. hystrix, decreasing the medium salinity to 20 caused granular cellular contents and concentrated chloroplasts (Aizdaicher and Markina, 2010). Meanwhile, photosynthetic performance and cell division were severely inhibited (Rijstenbil et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Salinity is a primary factor influencing the growth of marine microalgae, as algae often have a negative response in morphology and physiology during the salinity fluctuation (Al‐Hasan et al 1987, 1990; Aizdaicher et al 2010). Takagi et al (2006) reported that high salinity inhibited the growth, lipid and triacylglyceride accumulation of Dunaliella .…”
mentioning
confidence: 99%
“…60 Therefore, to obtain reliable interspecific comparisons, the use of data from cells well adapted to experimental salinity should be prioritized. In marine microalgae adapted to increased salinity, cell volume has been found to decrease in the haptophyte D. vlkianum VLP (Cañavate and Fernández-Díaz unpublished data), in diatoms, [61][62][63][64] the Prasinophyte Tetraselmis suecica, 10 the dinoflagellate Heterocapsa circularisquama 65 and even in the rigid cell walled species N. oceanica 66 and Microchloropsis gaditana. 67 This trend was also described in the estuarine diatoms Thalassiosira pseudonana 68 and Cyclotella meneghiniana.…”
Section: Theinter Ac Tingeffec Tof Salinit Yandculturecond Iti On Son Lipidcontentinmi Croalg Aementioning
confidence: 99%